NAHDATUL ULAMA (NU), DARI ORGANISASI KE POLITIK: 1952-1973 - Khoirun Nikmah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Nahdatul Ulama (NU) cannot be separated from Indonesian National History. The rapid development of NU cannot be separated from the role of kiai and Islamic boarding school students. NU in politics cannot be underestimated. In 1955 the NU Party was one of the winners of the election. The victory of the NU Party was repeated in 1971, winning the election after Golkar. However, the New Order government implemented a fusion policy that limited the existence of the Nu Party. From this incident, two problems emerged, namely 1) How did NU go from a religious organization to a political party? 2) How did the NU Party merge into the United Development Party (PPP)? The research method to be used is library research (literature review) with a qualitative-explorative approach. The conclusion of the results of this study is that the journey of the NU party brought extraordinary results with its winning achievements in the 1955 election. However, the NU party had to give up its existence because of a government regulation in 1973 implementing the fusion of political parties. The NU party must be willing to join the United Development Party (PPP). At that time NU's position in PPP was rarely heard by the government. NU figures in PPP were evicted from running for members of the DPR-RI. The fusion of political parties does not side with NU. Within Nu, conflicts often occur between NU clerics and politicians.